Analysis of visible light communication (VLC)for biomedical application - Yogeeswaran, S; G P, Ramesh (International Journal of Engineering and Technology, 2018)
In the visible light communication (VLC), light emitting diodes (LEDs) are used as transmitters; the air is the transmission medium and the photodiodes are used for receivers. This is often referred to as light fidelity (Li-Fi). In this method, provide the methodology to evaluate the performance of VLC hotspot networks in the context of data downloading on the move scenarios by using throughput-distance relationship models. In this context, firstly, study the different properties of optical transceiver elements, noise sources, characterization interference, and different link topologies and then introduce the throughput-distance relationship model. Secondly, the analytically based throughput-distance relationship has been developed for evaluating the performance of VLC hotspot networks in indoor environment in both day and night conditions. Simulation results reveal that background noise has a significant impact on the performance of VLC hotspots. As expected, in both indoor and outdoor environments VLC hotspot performs better at night than during the day. The performance of VLC hotspot networks is also quantified in terms of received file size at different bit error rate requirements and velocities of the mobile user.Â Â